The Effect of The Problem-Based Learning Model Assisted by E-LKPD to Improve Students' Learning Outcomes - Fatina, Gina Harnum Fatina; Safitri, Dian; Syafmal, Modyiksa Amelia (Indonesian Journal of Educational Innovation, 2025)
Innovative learning approaches are crucial for enhancing student learning. Outcomes, especially for materials that require deep conceptual understanding. This study aims to examine the effect of the Problem-Based Learning (PBL) model, assisted by Electronic Learning Knowledge and Problem-Based Teaching (E-LKPD), on enhancing student learning outcomes. The research employed a one-group pretest-posttest design, where students were given a pretest before and a posttest after the implementation of the PBL model assisted by E-LKPD. Quantitative data analysis, utilizing statistical tests, was conducted to determine whether there were significant improvements in student test scores. The results showed a substantial increase in posttest scores compared to pretest scores, indicating the effectiveness of the PBL model supported by E-LKPD in improving student learning outcomes. In conclusion, the PBL approach, combined with ELKPD, can be an effective alternative learning strategy for deepening students’ conceptual understanding. The scientific implication of this study highlights the importance of integrating digital technology into problem-based learning models to enhance the quality of science education.